UNWE STUDENTS’ ATTITUDE TO THE ONLINE FORM OF TRAINING IN TABLE TENNIS - E. Moneva (Trakia Journal of Sciences)
Our society is undergoing changes that place serious challenges before the entire world. In the current conditions of continuing education, the essence, role, methods and technology of education at higher education institutions are also changing. Online forms of learning and education are replacing the traditional methods. In the period from March 16 to March 24 2021, we made a survey among the students at the University of National and World Economy (UNWE) to find out their Attitude to the online form of training in Table Tennis. The aim of our survey was to obtain information about the opinion of the students at UNWE regarding the outcomes of the online training programs in Table Tennis. METHODS OF STUDY: Special survey cards were designed which included closed-ended questions. THE RESULTS: A large part of the students accept the combined form of training in Table Tennis. CONCLUSIONS: These conclusions give us the opportunity to plan, organize, and implement a study on the combined forms of training in Table Tennis with the students at UNWE.